PENGGUNAAN VIDEO SCRIBE UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK DONGENG SISWA KELAS V MIN 3 TANA TORAJA KECAMATAN MENGKENDEK KABUPATEN TANA TORAJA - Sry Hardini Tandiea Paembonan; M. Agus; Rahmatiah (STKIP Subang, 2024)
This research aims to describe improving the quality of fairy tale listening skills through video scribes in class V MIN 3 Tana Toraja, Mengkendek District, Tana Toraja Regency. This type of research is classroom action research (Class Action Reaserch) which consists of two cycles where each cycle is carried out as three meetings. Research procedures include planning, implementing actions, observing, reflecting. The subjects of this research were 12 students of class V MIN 3 Tana Toraja, Mengkendek District, Tana Toraja Regency. The results achieved in this research are: (1) There was an increase in student learning activities in each cycle. (2) In the first cycle, the average score for student learning outcomes was 55, while in the second cycle it was higher, reaching 84.16. In cycle I, there were 2 students or 16.7% who achieved learning completeness, while in cycle II there were 10 students or 83.3% who achieved learning completeness. Based on the results of the research above, it can be concluded that the results of learning listening skills for class V MIN 3 Tana Toraja students, Mengkendek District, Tana Toraja Regency, Mengkendek District, Tana Toraja Regency have increased.